2014
DOI: 10.1097/shk.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

Salutary Effect of Aurintricarboxylic Acid on Endotoxin- and Sepsis-Induced Changes in Muscle Protein Synthesis and Inflammation

Abstract: Small molecule nonpeptidyl molecules are potentially attractive drug candidates as adjunct therapies in the treatment of sepsis-induced metabolic complications. As such, the current study investigates the use of aurintricarboxylic acid (ATA), which stimulates insulin-like growth factor (IGF)-I receptor and AKT signaling, for its ability to ameliorate the protein metabolic effects of endotoxin (LPS) + interferon (IFN)γ in C2C12 myotubes and sepsis in skeletal muscle. ATA dose- and time-dependently increases mTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This compound -which has the propensity to polymerization in aqueous solution, forming a stable free radical that has been shown to inhibit various protein-nucleic acid interactions -has previously been shown to possess a number of pharmacological activities, including protease inhibition, complement inhibition, ribonuclease inhibition and neuraminidase inhibition [56][57][58][59][60]. It has also been shown to stimulate insulin-like growth factor 1 receptor, AKT and ERK signaling [61][62][63]. The stimulation of cell proliferation by aurintricarboxylic acid observed in our experiments -similar to previously observed stimulation of cell proliferation of various cell lines by this compound [64][65][66] may be related to the ability of the compound to stimulate var- ious proliferative signaling pathways; we hypothesize that these actions are more predominant in HCT116 cells that any antiproliferative effects that would be expected via CBS inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound -which has the propensity to polymerization in aqueous solution, forming a stable free radical that has been shown to inhibit various protein-nucleic acid interactions -has previously been shown to possess a number of pharmacological activities, including protease inhibition, complement inhibition, ribonuclease inhibition and neuraminidase inhibition [56][57][58][59][60]. It has also been shown to stimulate insulin-like growth factor 1 receptor, AKT and ERK signaling [61][62][63]. The stimulation of cell proliferation by aurintricarboxylic acid observed in our experiments -similar to previously observed stimulation of cell proliferation of various cell lines by this compound [64][65][66] may be related to the ability of the compound to stimulate var- ious proliferative signaling pathways; we hypothesize that these actions are more predominant in HCT116 cells that any antiproliferative effects that would be expected via CBS inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of cell proliferation by aurintricarboxylic acid observed in our experiments -similar to previously observed stimulation of cell proliferation of various cell lines by this compound [64][65][66] may be related to the ability of the compound to stimulate var- ious proliferative signaling pathways; we hypothesize that these actions are more predominant in HCT116 cells that any antiproliferative effects that would be expected via CBS inhibition. Although its mode of action and its diverse pharmacological effects suggest lack of specificity (and perhaps lack of in vivo utility) surprisingly, aurintricarboxylic acid is tolerated in experimental animals, and, in fact, has been shown to produce therapeutic benefits in a variety of conditions including encephalitis and sepsis [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, there was no information on effects of dietary selenium, in particular high selenium intake, on body protein metabolism, although protein synthesis was reported to negatively regulate insulin sensitivity (20,21) and a high protein diet inhibited the development of type 2 diabetes (22). Mammalian target of rapamycin (mTOR), ribosomal protein S6 kinase (P70), ribosomal protein S6 (S6), factor 4E binding protein 1 (4EBP1), and eukaryotic translation initiation factor 4E (EIF4E) are key factors involved in the protein synthesis pathway (23)(24)(25)(26)(27). Furthermore, AMP-activated protein kinase (AMPK) plays a key role in regulating energy metabolism (28) and showed a negative association with selenium intake in rats (29).…”
Section: Introductionmentioning
confidence: 99%
“…In this work we have used ATA to inhibit the function of PMCA4. The feasibility of ATA as a clinical treatment has yet to be tested, but pre-clinical studies in animal models have revealed potential clinical applications in the treatment of cardiac hypertrophy [27], experimental autoimmune encephalomyelitis [43], sepsis [22], and myocardial ischaemia-reperfusion injury [44].…”
Section: Discussionmentioning
confidence: 99%